An approach to determining homogeneity in taxonomic breadth of periphytic ciliate communities in colonization surveys for bioassessment. (December 2019) - Nurul Azim Sikder, Mohammad; Bai, Xiaoyun; Warren, Alan; Xu, Henglong
Highlights: Temporal variations in taxonomic distinctness differed among four water depths. Homogeneity in taxonomic structure of the ciliate communities was high at depths of 1 and 2 m. Homogeneity of mature ciliate communities showed a decreasing trend from a depth of 1 to 5 m. Taxonomic distinctness indices were a useful tool to detemrmine homogeneity of ciliate samples. This approach facilitates development of optimal sampling strategies for bioassessment. Abstract: Taxonomic distinctness is powerful tool to test the departure of a community from an expected pattern of taxonomic structure in response to environmental change. To determine the homogeneity in taxonomic breadth of periphytic ciliates, a 1-month baseline colonization survey was conducted in Jiaozhou Bay, near Qingdao, northern China, using glass slides as artificial substrates. A total of 240 slides were collected at depths of 1, 2, 3.5 and 5 m after colonization periods of 3, 7, 10, 14, 21 and 28 days. The taxonomic composition and structure of the periphytic ciliate communities differed among the four water depths. The temporal variations in all four taxonomic diversity/distinctness measures had different patterns of variability at each depth. Ellipse test on the pairs of average taxonomic distinctness ( Δ + ) and variation in taxonomic distinctness ( Λ + ) demonstrated a spatial variability in homogeneity in taxonomic structure of the ciliate communities from 1 m to 5 m, with high levels at 1 and 2 m compared to those at the other two depths. These results suggest that taxonomic distinctness is a useful indicator to identify the homogeneity in taxonomic breadth of periphytic ciliate communities during the colonization process in marine ecosystems.